Cannulation of the coronary sinus via the femoral vein—A new technique - Katritsis, Demosthenes (Clin Cardiol, 2009)
Background: Cannulation of the coronary sinus usually has been accomplished by advancing a catheter through the subclavian or internal jugular veins. Hypothesis: We have developed a new technique for cannulation of the coronary sinus with a modified 6F Judkins L5 coronary catheter positioned through the femoral vein. Results: The technique was tried successfully in 20 consecutive patients by the same operator and the average fluoroscopy time for coronary sinus cannulation was 1.6 ± 1.0 min. Conclusion: Analysis of the results showed evidence of a learning curve with improvement of time with an increasing number of patients. The method provides a safe and inexpensive solution for catheterization of the coronary sinus, easily accessible to every catheter laboratory.